Tia Maria mining project: reasons for the protest - Pinto Herrera, Honorio (2017)
This article is about the Tia Maria mining project ( PMTM ) Company Southern Copper Corporation (Group Mexico). The subject is vast and complex; for this reason and because of space limitations here only the reasons that generated protests from residents of Valle de Tambo (VDT) develops. Is selected, among others, the following sub-themes: environmental impact assessment, water, agriculture, wind direction, mining facilities, workshops and public hearings, finally the negative legacy of the Southern.